Muscle Power and Body Composition of Ranked and Unranked Brazilian Jiu-Jitsu Athletes: A Pilot Study - Adriano Neves Breithaupt; Ricardo Luís Fernandes Guerra (Applied Sciences)
Background: Brazilian Jiu-Jitsu (BJJ) is a martial art in which practitioners require a variety of technical and biomotor skills for optimal performance. The International Brazilian Jiu-Jitsu Federation (IBJJF) awards points to athletes who win first, second, and third place in their competitions, but it is not known whether there are differences between ranked and unranked athletes. Therefore, the objective was to evaluate and compare the muscular strength and body composition of IBJJF-ranked and unranked athletes. Methods: Eight athletes ranked (RG = 3–1st, 24th, and 26th) or not (NRG = 5) by the IBJJF participated in this study and underwent lower and upper limb power and body composition tests. Results: despite percentage differences in favor of RG, there were no differences (p > 0.05) between the groups for the variables analyzed. Conclusions: there is no difference in muscular power and body composition between ranked and unranked athletes. This state of affairs suggests the complexity of athletic performance in Brazilian Jiu-Jitsu (BJJ) and thus highlights the need to consider other aspects in addition to those evaluated, such as technique, tactics, and psychological factors, which can play a crucial role in the performance of athletes.